POTENSI PRODUKSI HIJAUAN DAN KOMPOSISI KIMIA RUMPUT SUDAN (Sorghum sudanense) SEBAGAI SUMBER HIJAUAN PAKAN LOKAL DI WILAYAH PAPUA - Onesimus Yoku (Udayana University, 2016)
This paper aims to provide an overview of the potential forage production, nutrients and antinutrients chemical composition, and the potential development of Sudan grass (Sorghum sudanense) in eastern part of Indonesia, particularly in the Papua island as a local forage ruminant. Local forage is very potential to be developed in Papua island, because it adapts to dry land and drought resistant, capable of growing back, and is very responsive to fertilizer and irrigation, as well as can be growth either in lowland and highland. Nitrogen, phosphorus and potassium fertilizer treatments have significant effect to dry matter and organic matter productions of Sudan grass with their level dosage recommendations are 300 kg N/ha, 300 kg P/ha, and 150 kg P/ha, respectively. Keywords: sudan grass, fertilizer, forage production, nutrient and antinutrition